A novel aerogel sodium‐based sorbent for low temperature CO2 capture. Issue 4 (10th February 2016) - Yu, Fan; Wu, Ye; Zhang, Wenjing; Cai, Tianyi; Xu, Yuhao; Chen, Xiaoping
Abstract: The object of this research is to develop a novel sodium‐based solid sorbent with amine modification for low temperature CO2 capture in coal‐fired power plants. The new sorbent (NaN) was synthesized with Na2 CO3, 3‐aminopropyltriethoxysilane (APTES) and tetraethylorthosilicate (TEOS) through sol‐gel method, and then dried with three different methods: conventional drying (CD), organic solvent sublimation drying (OSSD), and supercritical fluid drying (SCFD). The CO2 sorption capacity of NaN was evaluated using a fixed‐bed reactor under various conditions including the temperature and moisture concentration of the flue gas. Results demonstrated that the optimized SCFD‐NaN with APTES:Na2 CO3 :TEOS mole ratio of 1:1:1 reached the highest CO2 sorption capacity of 2.51 mmol/g under the best experimental conditions (50°C, H2 O/CO2 = 1:1). Moreover, the NaN sorbent was regenerable and stable during the 10 cyclic operations. Thus, the SCFD‐NaN sorbent is a promising composite sorbent for CO2 capture. © 2015 Society of Chemical Industry and John Wiley & Sons, Ltd